Comparing impact of multi-factor planning layouts in residential areas on summer thermal comfort based on orthogonal design of experiments (ODOE). (September 2020) - Yang, Shuhan; Zhou, Dian; Wang, Yupeng; Li, Po
Abstract: The previous studies of outdoor thermal comfort mainly focused on the micro-climate changes caused by urban morphological factors such as street aspect ratio, plot ratio, sky view factor (SVF) et al. As an essential routine to mitigate urban heat island (UHI), vegetation was also discussed by researchers to explore the optimal distribution. However, under the same determined quantity, there is still a blank of the study in how significant each layout factor is to thermal comfort, including the building layout, the pavement layout, and the vegetation layout. This paper followed an orthogonal design of experiment (ODEO) to create various multi-factor layouts in the case of northern China, thoroughly analyzing simulated results based on Physiological Equivalent Temperature (PET) to explain the internal mechanism. Results show that in high-rise residential areas, the layout significance ranking affecting thermal comfort in summer is: buildings, vegetation, pavement. The optimal arrangement is a layout combination of the scattered-form buildings, the grid-form pavement, and the southern vegetation, which can reduce PET of 6.3% maximally during the day. We also found that wind maps are highly consistent with PET maps due to its heat dissipation capability. Another reason for the high PET value is the solar radiation trapping effect, which should be considered with building shade when discussing the relationship between multi-layouts and thermal comfort. The arrangement method can provide a new research direction of urban micro-climate in the future and thus can be employed by decision-makers in the early planning stage. Graphical abstract: Image 1 Highlights: ODED introduced for non-quantitative factors comparison. A layout study under the same quantity of buildings, pavement, and vegetation. The layout of vegetation has less impact on PET than buildings, followed pavement. Scattered-form buildings, grid-form pavement, southern vegetation, best for PET. Solar radiation trapping and ventilation trigger PET differences among layouts.